Implementation of 21st Century Skills in Informatics Subjects by Applying Google Sites for 9th Grade Students at SMPN 6 Darangdan - Muhammad Musyaffa; Nuur Wachid Abdul Majid (Journal of Educational Sciences, 2026)
21st-century education demands the integration of technology to develop 6C skills contextually. This study aims to describe the implementation of Google Sites in supporting 6C skills in ninth-grade Informatics learning at SMP Negeri 6 Darangdan. The study used a qualitative approach with a single case study design. Data were obtained through observation, in-depth interviews with the principal, teachers, and five students, as well as documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that project-based learning through Google Sites was able to develop critical thinking and creativity through digital content design, and strengthen collaboration and communication through teamwork and presentations. The dimensions of character and citizenship were internalized through ethical digital publication practices. However, structural obstacles were found in the form of limited infrastructure and technical readiness. It was concluded that the effectiveness of strengthening 6C is more determined by reflective pedagogical design than the complexity of the technology used.